The role of self-learning in the practical training among preschool teachers - Nataliia Honchar; Nataliia Мyskova; Nataliia Kazakova; Larysa Zdanevych; Leonida Pisotska (Institute of Advanced Engineering and Science, 2022)
The article examines conditions for effective implementation of self-learning program in the training preschool teachers. The following research methods were used: pedagogical experiment, testing, observation, activity analysis, Kolmogorov-Smirnov test, Student’s t-test. An independent variable of the experiment was the self-learning program of preschool teachers developed through quality feedback and self-analysis. The professional competence of preschool teachers is studied through a system of components: motivational, cognitive, activity and reflective. Motivational and reflective components are less developed than cognitive and activity ones. It was found that the self-learning program is more effective for the development of cognitive, activity and reflective components, while the motivational component was less developed. It is established that the basic conditions for the effectiveness of professional self-learning is feedback from the program developer and ensuring quality pedagogical reflection of one’s actions. The following blocks of material were the most problematic for the assimilation of in the developed course: the physiological characteristics of children, speech and thinking of preschoolers, various aspects of the organization of learning and play in preschool education. The data can be used in the self-learning practice of preschool teachers and students to stimulate professional development. Further prospects for the study of the problem include improving the self-learning program for implementation in higher educational institutions. It is important to optimize the ways of development of preschool teachers’ pedagogical reflection. The development of standardized forms of assessment of acquired competencies is worth noting.